In silico exploration of Elaeocarpus ganitrus extract phytochemicals on STAT3, to assess their anticancer potential - Mehnaj; Abdul Roouf Bhat; Fareeda Athar (Medicinal Plant Biology)
Elaeocarpus ganitrus Rox of the Elaeocarpaceae family is a broad-leaved medicinal plant and exhaustively used in orthodox systems of treating diseases. However, its anticancer impact and propensity to STAT3 has not yet been analyzed. The plant's extracts were in vitro assayed on the HeLa cell line and subsequently, GC-MS chromatogram of the methanolic, and chloroform extracts of the plant revealed that 106 compounds were present in the extracts. Subsequent filtration using Lipinski rules resulted in 81 phytochemicals being selected for the docking process with pre-selected receptor STAT3 (6NJS). Twenty-six out of 81 phyto-ligands showed high binding energy. Many drugs have weak pharmacokinetic properties and cellular toxicity and consequently, cannot pass through clinical trials. Hence, it is essential to determine the pharmacokinetic parameters of the phytoligands showing preferred binding with receptor 6NJS to consider the apparent bioavailability. The data for pharmacokinetics behavior, bioavailability extent, drug-likeness properties, medicinal chemistry friendliness, and toxicity of 26 phytochemicals with referenced inhibitors was explored. These 26 compounds were further checked for their ADMET properties by using the swissADME and PROTOX-II web server with the known inhibitors plumbagin and sanguinarine to determine the lead phytocompounds. The predictions of ADMET properties obtained six suitable phytocompounds (EG-9, EG-12, EG-13, EG-15, EG-16 and EG-26) of E. ganitrus, and found to be a perfect fit in the bioavailability radar. 2D and 3D interaction of phytoligands with the STAT3 show that the binding is through lys97, suggesting NH2-terminal domain binding of STAT3 with ligands which is the main mono-ubiquitin conjugation spot. Most of the phytoligands interactions exist in the Linker domain and Transactivation domain of the STAT3.